Health in Metaphysics Perfective - Syarifuddin Syarifuddin (Budapest International Research and Critics University, 2022)
This research discusses health from a metaphysical perspective. The method used in this research is qualitative research design. The results of this study indicate that by studying health from a metaphysical perspective, it opens the curtain that unfurls the secrets of the soul, spirit and other spiritual tools, thereby encouraging us to study metaphysics so that we become healthy people physically and mentally who are able to incarnate justice, prosperity life of a nation and state, as well as being able to provide prosperity in this world and the hereafter.